1996
DOI: 10.1007/bf00202886
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytes carry the fused bcr-abl gene in chronic myeloid leukaemia: a fluorescence in situ hybridization analysis from bone marrow biopsies

Abstract: Histological examination of bone marrow biopsies shows that about one-third of chronic myeloid leukaemia (CML) patients exhibit an increase of megakaryocytes. The megakaryocytic predominance may be so striking that differentiation from other chronic myeloproliferative disorders (CMPD) may be difficult in some CML patients. Megakaryocytes in CML are clonal as demonstrated by loss of glucose-6-phosphate dehydrogenase isoenzymes. The Ph translocation, fusing the abl and bcr genes on chromosomes 9 and 22, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…[10] showed that not only the transforming event but also the Ph + translocation leading to BCR-ABL + fusion happens prior to the differentiation of the pluripotent stem cell into different myeloid lineages.…”
Section: Discussionmentioning
confidence: 99%
“…[10] showed that not only the transforming event but also the Ph + translocation leading to BCR-ABL + fusion happens prior to the differentiation of the pluripotent stem cell into different myeloid lineages.…”
Section: Discussionmentioning
confidence: 99%
“…2,[42][43][44][45] There is some controversy over whether lymphocytes are of leukemia origin in CML. Garicochea et al 46 reported that T lymphocytes had no bcr/abl fusion gene, while Tefferi et al 42 demonstrated that t(9;22) was detectable in 34% of CD3-positive T lymphocytes, in 32% of CD19-positive B lymphocytes and in 82% of CD34-positive precursor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Biotin is covalently linked to the C-5 position of dUTP (Langer et al 1981), but can also be chemically coupled to other nucleotides such as adenosine and cytosine (Gebeyehu et al 1987). Biotinylated probes are detected by the avidin or streptavidin method or less frequently by anti-biotin antibodies (Cremer et al 1986;Hopman et al 1986b;Nolte et al 1996a). The sensitivity of the former method can be further enhanced by the use of a bridging anti-avidin antibody followed by a second round with fluoresceinated avidin (Waldman et al 1991;Kim et al 1993;Nasarek et al 1995).…”
Section: Detectionmentioning
confidence: 99%
“…If proteolytic pretreatment is used to demask the genomic DNA, this step has to be optimized for different tissues and fixation times. Perhaps more reliable and reproducible results, especially for the detection of single copy genes in thin paraffin sections, have been obtained by boiling the sections in citric buffer prior to FISH (Nolte et al , 1996a. This pretreatment, that is easily performed in a microwave oven, can be standardized, in contrast to enzymatic digestion, which has to be titrated (Werner et al 1996).…”
Section: Cytological Preparationsmentioning
confidence: 99%